Y–Z in the labour market: employee perceptions in different cultures (Hungary–Pakistan) - Bencsik, Andrea; Shujahat, Ali; Juhász, Tímea (Business: Theory and Practice, 2021)
Research on generations examine and analyse the similarities and differences between various age groups, and their opportunities for cooperation in the labour market, from various perspectives. According to the research, the behaviour and preparedness of each generation are different, the coordination and proper management of which poses challenges for all organisations. This is especially true when staff from national cultures with very distant values work together. The recognition of this problem was the pretext to the present research. The aim of the research is to examine the perception of the under 30 age group socialised and employed in two largely different cultures (Hungarian–Pakistani). Contrary to our assumption, the results of the quantitative research based on an online questionnaire confirm that the respondents do not perceive differently the behaviour, attitudes, expectations regarding work, workplace and employers of Pakistani and Hungarian young people at work. Employers’ perceptions of this age group play a significant role in choosing the tools that affect their retention in the workplace. In this respect, the employees of the studied cultures find similar solutions expedient.